The Motion and Range of Landslides According to Their Height - Li, Heng; Duan, Zhao; Wu, Yanbin; Dong, Chenxi; Zhao, Fasuo (Frontiers in Earth Science, 2021)
The frequency of catastrophic geological disasters has been increasing significantly, causing tremendous losses of life and property. The study of landslide motion remains incomplete. The variables H/L (ratio of landslide height to length) are often used to describe landslide motion; however, they may also be affected by the height of the landslide itself. To better understand landslide dynamics, this paper aimed to 1) identify the process of landslide motion in relation to height; 2) understand the range of influence of sliding bodies according to height; and 3) construct a formula of landslide disaster range based on the travel distance of the slide center and changes in the center and shape of the sliding body. In this paper, medium-fine quartz sand was used in experiments to observe the movement patterns and sliding body barycenter variations occurring during landslides. We describe the changes that occur during landslides and their deposits’ morphological characteristics and barycenter variations with height. Based on these observations, a landslide model is derived. This paper proposes a new method of estimating the effects of landslides, which can help to mitigate the effects of disasters.